Aspectos sociales de la jornada laboral y el despido sin causa justificada. Constitución de 1979 y constitución de 1993 del Perù (Società e diritti, 2023)
AbstractThe background of the recognition in Perú of the working day is exposed and the affectation to the fundamental rights of the arbitrary dismissal is analyzed as they are legislated in the constitutions of Peru of 1979 and that of 1993 currently in force. The economic context is examined as a condition in the regulation of dismissal without cause. Labor costs and fundamental rights. The judicial protection of the worker dismissed without cause, contrasting constitutional jurisprudence versus labor jurisprudence